Monochorea after acute contralateral pontine infarction: A case report. Issue 3 (20th January 2023) - Hwang, Yun Su; Shin, Byoung-Soo; Ryu, Han Uk; Kang, Hyun Goo
Abstract : Rationale: Chorea is a hyperkinetic movement characterized by random, brief, and involuntary muscle contractions. In stroke, a common cause of chorea, basal ganglia are anatomical locations that can cause chorea when a stroke occurs, and chorea is less frequently triggered by a stroke in other anatomical brain regions. Herein, we report a rare case of monochorea after acute contralateral pontine infarction. Patient concerns: A 32-year-old man visited the emergency room due to dysarthria and right hemiparesis that occurred approximately 6 hours and 30 minutes before the visit. A brain magnetic resonance image confirmed a diffusion restriction lesion in the left pons. The patient was initially diagnosed with acute infarction at the left pons and began to receive medical treatment with an antiplatelet agent and statin with admission. Diagnosis: Approximately 14 hours after the onset of the initial stroke symptoms, the patient complained of involuntary movement in the right arm for the first time. Intermittent, irregular involuntary movements were observed in the distal part of the right arm. This symptom was unpredictable and random, and a similar symptom was not observed in other parts of the patient's body. Clinically, post-stroke monochorea was suspected. Interventions and outcomes: The symptom improved from day 5 without specific medical treatment for chorea. Lessons: The monochorea caused by the pontine lesion in this case was triggered by the direct lesions of the corticospinal tract, and its underlying pathophysiology remains unclear. However, abnormal movements can occur due to inadequate downstream activation or inhibition of the corticospinal tract, which is induced by functional abnormalities of the motor cortex. This case suggests that further investigation is needed on the mechanisms of direct corticospinal tract lesions for chorea.